Interpregnancy Body Mass Index Changes: Distribution and Impact on Adverse Pregnancy Outcomes in the Subsequent Pregnancy - Bender, Whitney; Hirshberg, Adi; Levine, Lisa D. (American Journal of Perinatology, 2019)
Objective To examine the change in body mass index (BMI) categories between pregnancies and its effect on adverse pregnancy outcomes.Study Design We performed a retrospective cohort study of women with two consecutive deliveries from 2005 to 2010. Analysis was limited to women with BMI recorded at <24 weeks for both pregnancies. Standard BMI categories were used. Adverse pregnancy outcomes included preterm birth at <37 weeks, intrauterine growth restriction (IUGR), pregnancy-related hypertension, and gestational diabetes mellitus (GDM). Women with increased BMI category between pregnancies were compared with those who remained in the same BMI category.Results In total, 537 women were included, of whom 125 (23%) increased BMI category. There was no association between increase in BMI category and risk of preterm birth, IUGR, or pregnancy-related hypertension. Women who increased BMI category had an increased odds of GDM compared with women who remained in the same BMI category (6.4 vs. 2.2%; p = 0.018). The increased risk remained after controlling for age, history of GDM, and starting BMI (adjusted odds ratio: 8.2; 95% confidence interval: 2.1–32.7; p = 0.003).Conclusion Almost one-quarter of women increased BMI categories between pregnancies. This modifiable risk factor has a significant impact on the risk of GDM.
Keywords: body mass index; interpregnancy weight gain; gestational diabetes